Potret Ragam Bahasa Lisan Di Pasar Citra Niaga Samarinda, Kalimantan Timur - Wahab, Muhammad Abdul; Zahra, Aghist Muflihah (CV. ITTC INDONESIA, 2022)
Each community has its own pattern of communication. These patterns can eventually form a variety of languages. Handayani (2019: 5) states that various languages are variations of language that can be distinguished according to usage, topics discussed, the relationship between the speaker, the person he is talking to, the person being talked about, and the medium of the speaker. This study aims to find out the portrait of the interaction of various spoken languages in the Citra Niaga Samarinda market area, East Borneo, amidst the strong flow of modernity. This research belongs to the type of field research in which researchers obtain direct data from the Citra Niaga Samarinda market area for further review. Data collection was carried out by observation and documentation techniques. The recorded data was transcribed into written form and then sorted according to categorization. Furthermore, the data was analyzed using the matching method. The results of this study were in the form of data on the variety of languages which were qualified based on age, context, and the tendency to use regional languages. There are three kinds of languages found in the Citra Niaga Samarinda area, including Indonesian, Javanese, and Banjarese. Based on the number of speakers, Indonesian is the most common language, followed by Javanese, then Banjar. The use of code switching from local languages to Indonesian by speakers proves that Indonesian is accepted by the people in the Citra Niaga area.